Direct Catalytic Conversion of Biomass-derived Carbohydrates to Ethyl Levulinate - Shan, Jianrong; Hao, Hengyu; Shen, Feng; Yang, Jirui; Qiu, Mo; Wang, Ruigang; Guo, Haixin (Current Organic Chemistry, 2023)
Recently, levulinic acid as an important bio-based platform compound has attracted wide attention, and its potential application value is very high. This article focuses on chem-catalytic produced ethyl levulinate (EL) from biomass-derived carbohydrates (C6 carbohydrates) via multiple reaction pathways, which has an energy density comparable to gasoline and has great potential as a fuel additive. This review focuses on recent examples of the synthesis of EL from various materials using homogenous or heterogeneous catalysts. Special emphasis is placed on the understanding of the reaction mechanism and pathways. This review also summarizes the future opportunities and challenges associated with the applications of EL as a fuel additive and in other fields.
Keywords: biomass conversion